Electrospinning of Hyaluronan Using Polymer Coelectrospinning and Intermediate Solvent - Vítková, Lenka (Polymers (Basel), 2019)
In the current study, we present methods of sodium hyaluronate, also denoted as hyaluronan (HA), nanofiber fabrication using a direct-current (DC) electric field. HA was spun in combination with poly(vinyl alcohol) (PVA) and polyethylene oxide (PEO) and as a pure polymer. Nonaggressive solvents were used due to the possible use of the fibers in life sciences. The influences of polymer concentration, average molecular weight ([Formula: see text]), viscosity, and solution surface tension were analyzed. HA and PVA were fluorescent-labeled in order to examine the electrospun structures using fluorescence confocal microscopy. In this study, two intermediate solvent mixtures that facilitate HA electrospinning were found. In the case of polymer co-electrospinning, the effect of the surfactant content on the HA/PVA electrospinning process, and the effect of HA [Formula: see text] on HA/PEO nanofiber morphology, were examined, respectively.